The treatment for closure of the bladder neck via transvaginal approach - Castro, Alejandra A.; Gonzalez, Guillermo A.; Gomez, Andrea M.; Santiago, Gerardo G.; Perez, Mariano B. L.; Quevedo, Mauricio M.; Alba, Maria P.; Cuellar, Rodrigo M. (International Surgery Journal, 2023)
Urinary incontinence is described as the involuntary loss of urine due to an increase in intra-abdominal pressure combined with a lack of contraction of the detrusor muscle. The most common being stress incontinence, as it occurs in 30% of women between 30 and 60 years old. There is another condition called hidden stress incontinence as a result of a coiling of the urethra that causes obstruction in its lumen. This can manifest itself when performing any activity that involves effort, such as coughing or sneezing. Nowadays there are numerous surgical interventions for the treatment of these pathologies, so there is a discrepancy in the choice of the appropriate surgical technique to correct these conditions in isolation.